Implicit contracts and industrial relations - Evidence from German employer-employee data - Gartner, Hermann (Economics Bulletin, 2015)
I test the evidence for implicit contracts across different regimes of industrial relations in Germany. The result is that there is strong evidence for implicit contracts. Comparing regimes of industrial relations, I find stronger support for implicit contracts in firms with individual bargaining and when a works council exists.